2020
DOI: 10.1186/s40729-020-00266-y
|View full text |Cite
|
Sign up to set email alerts
|

Guided bone regeneration in staged vertical and horizontal bone augmentation using platelet-rich fibrin associated with bone grafts: a retrospective clinical study

Abstract: Background The use of guided bone regeneration (GBR) for vertical and horizontal bone gain is a predictable approach to correct the bone defects before implant installation; however, the use of different protocols is associated with different clinical results. It is suggested that platelet-rich fibrin (PRF) could improve the outcomes of regenerative procedures. Thus, this study aimed to describe the bone gain associated with GBR procedures combining membranes, bone grafts, and PRF for vertical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
47
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(47 citation statements)
references
References 39 publications
0
47
0
Order By: Relevance
“…The complications rate was 8.4%, while five studies did not report any type [ 16 , 19 , 24 , 25 , 27 ]. The 11 remaining studies demonstrate some clinical complications, including: membrane exposure, the most frequent (15 membranes exposures in seven studies [ 17 , 21 , 23 , 26 , 28 , 29 , 30 ]); nine dehiscences were reported in three studies [ 18 , 20 , 22 ]; two manuscripts referred to one infection each [ 23 , 26 ] ( Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The complications rate was 8.4%, while five studies did not report any type [ 16 , 19 , 24 , 25 , 27 ]. The 11 remaining studies demonstrate some clinical complications, including: membrane exposure, the most frequent (15 membranes exposures in seven studies [ 17 , 21 , 23 , 26 , 28 , 29 , 30 ]); nine dehiscences were reported in three studies [ 18 , 20 , 22 ]; two manuscripts referred to one infection each [ 23 , 26 ] ( Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…Ten of the selected studies used autologous bone + xenogenic as bone substitute [ 16 , 18 , 19 , 20 , 21 , 23 , 24 , 25 , 26 , 30 ], from which, 70% used particulate autologous bone + xenograft [ 16 , 18 , 21 , 24 , 25 , 26 , 30 ], 20% used autologous bone block [ 19 , 23 ], and one study compared both techniques [ 20 ], concluding that mean horizontal bone gain and width after healing were significantly greater in the group of autologous particulate bone compared to bone block.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This liquid blood derivative is enriched with high concentrations of platelets, leukocytes, and growth factors [ 31 33 ]. Recent studies have reported that i-PRF provides a three-dimensional fibrin-dynamic gel embedded with platelets, leukocytes, type-I collagen, osteocalcin, and growth factors [ 31 ] with the potential to modulate inflammatory processes [ 34 ], exert anti-bacterium and anti-biofilm activities [ 35 , 36 ], and promote osteogenesis [ 37 39 ]. Compared to PRF, i-PRF results in better bone regeneration [ 39 ], treatment of gingival recession defects [ 40 ], and elimination of endodontic infection [ 36 ].…”
Section: Introductionmentioning
confidence: 99%